Local sourcing of raw materials for the manufacturing of manual metal arc welding electrodes: a case for locally produced steel wire in Nigeria (2008)
Since early 1995 when pressure was mounted on the Raw Materials Research and Development Council in Nigeria, with a view to sourcing wire, flux and binder locally, little or no success has been recorded. As at 1998, all the raw materials including core wire for electrode manufacture in Nigeria were still being imported. The aim of this project is therefore to explore the possibility of using locally sourced wire in electrode production. In this research, wire drawn at the Oshogbo rolling company in South Western Nigeria from billets produced at Delta Steel Company Aladja in Delta state, Nigeria was used with commercial flux in a production run by a local electrode manufacturing outfit. Mechanical tests and microstructure show that the quality of electrodes produced compared favourobly with E6010 standards.